Handbook of personality psychology (Academic Press, 1997)
The most comprehensive single volume ever published on the subject, the Handbook of Personality Psychology is the end-all, must-have reference work for personality psychologists. This handbook discusses the development and measurement of personality as well as biological and social determinants, dynamic personality processes, the personality's relation to the self, and personality in relation to applied psychology. Authored by the field's most respected researchers, each chapter provides a concise summary of the subject to date. Topics include such areas as individual differences, stability of personality, evolutionary foundations of personality, cross-cultural perspectives, emotion, psychological defenses, and the connection between personality and health. Intended for an advanced audience, the Handbook of Personality Psychology will be your foremost resource in this diverse field. Chapter topics include: * Nature of personality psychology * Conceptual and measurement issues in personality * Developmental issues * Biological determinants of personality * Social determinants of personality * Dynamic personality processes * Personality and the self * The Five Factor Model * Applied psychology